2021
DOI: 10.1080/14786419.2021.1876046
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative potential of moluccella laevis L. aerial parts family lamiaceae (labiatae), supported by phytochemical investigation and molecular docking study

Abstract: The current biologically guided study aimed the in vitro investigation of cytotoxic activity, identification the phytochemical content of Moluccella laevis L. aerial parts and supporting this activity by molecular docking study. Aqueous fraction demonstrated the most potent cytotoxic effect against CACO-2 with IC 50 = 0.067±0.05 μg/mL. Furthermore, EtOAc fraction showed a remarkable cytotoxic activity against MCF-7 cell line with IC 50 = 0.31±0.05 μg/mL. Consequently, total ethanolic extract (TEE) and its frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Additionally, 20 compounds were tentatively identified from LC-HR-ESI-MS metabolomic analysis. These compounds revealed that stachydrine is more likely to account for the cytotoxic activity of both the EtOAc and aqueous fractions in silico docking study [5]. Furthermore, 8 compounds: palmitic acid, tricosan-1-ol, pentadecan-1-ol, icosyl acetate, a mixture of sitosterol & stigmasterol, β-sitosterol-7-O-β-D-glucopyranoside and luteolin-7-O--D-glucopyranoside, were isolated and identified spectroscopically [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, 20 compounds were tentatively identified from LC-HR-ESI-MS metabolomic analysis. These compounds revealed that stachydrine is more likely to account for the cytotoxic activity of both the EtOAc and aqueous fractions in silico docking study [5]. Furthermore, 8 compounds: palmitic acid, tricosan-1-ol, pentadecan-1-ol, icosyl acetate, a mixture of sitosterol & stigmasterol, β-sitosterol-7-O-β-D-glucopyranoside and luteolin-7-O--D-glucopyranoside, were isolated and identified spectroscopically [5].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the antibacterial activity of TEE and its various fractions was studied against Gram-positive and Gram-negative bacteria [4]. Furthermore, both of the aqueous and EtOAc fractions of TEE demonstrated the most potent cytotoxic effect against cancer cell lines as CACO-2 and MCF-7, respectively [5]. Additionally, 20 compounds were tentatively identified from LC-HR-ESI-MS metabolomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the antibacterial activity of TEE and its different fractions was investigated against Gram-positive and Gram-negative bacteria [4]. Additionally, both the aqueous and EtOAc fractions of TEE demonstrated the most potent cytotoxic effect against immortalized cell lines of human colorectal adenocarcinoma (CACO-2) and human breast cancer cell lines (MCF-7), respectively [5]. Moreover, twenty compounds were tentatively identified from LC-HR-ESI-MS metabolomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, twenty compounds were tentatively identified from LC-HR-ESI-MS metabolomic analysis. In silico docking study for these compounds revealed that stachydrine is more likely to account for the antiproliferative activity of both the EtOAc and aqueous fractions [5]. Furthermore, eight compounds: palmitic acid, tricosan-1-ol, pentadecan-1-ol and icosyl acetate, a mixture of -sitosterol & stigmasterol, β-sitosterol-7-O-β-D-glucopyranoside and luteolin-7-O--D-glucopyranoside, were isolated [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation